Peran Pengeluaran Pemerintah pada Pembangunan Manusia: Model Efek Tetap (Studi Pada Kabupaten/Kota Di Provinsi Jawa Timur) - Faisol, Faisol; Krifiahurrohamah, Tyas Karmaylia (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
The purpose of this study is to justify the effect of government expenditure included operational expenditure, education expenditure, health expenditure, physical health facilities, physical education facilities on the human development. The object of this research consists of 38 districts/ cities in East Java from the 2015-2019 periode. The data used in this study is secondary data obtained from (www.djpk.kemenkeu.go.id) dan (www.bpsjatim.go.id). The analysis technique uses a regression model using panel data with STATA 14. The result of this research is that operational expenditure has effect significantly on HDI, education spending has no effect on HDI, health spending has no effect on HDI, physical education facilities has effect significantly on HDI, physical health facilities have no effect on HDI.